An fMRI Study of Neuronal Activation in Schizophrenia Patients with and without Previous Cannabis Use - Løberg, Else-Marie; Nygård, Merethe; Helle, Siri; Berle, Jan Øystein; Johnsen, Erik; Kroken, Rune; Jørgensen, Hugo; Hugdahl, Kenneth (Frontiers in Psychiatry, 2012)
Previous studies have mostly shown positive effects of cannabis use on cognition in patients with schizophrenia, which could reflect lower neurocognitive vulnerability. There are however no studies comparing whether such cognitive differences have neuronal correlates. Thus, the aim of the present study was to compare whether patients with previous cannabis use differ in brain activation from patients who has never used cannabis. The patients groups were compared on the ability to up-regulate an effort mode network during a cognitive task and down-regulate activation in the same network during a task-absent condition. Task-present and task-absent brain activation was measured by functional magnetic resonance neuroimaging (fMRI). Twenty-six patients with a DSM-IV and ICD-10 diagnosis of schizophrenia were grouped into a previous cannabis user group and a no-cannabis group. An auditory dichotic listening task with instructions of attention focus on either the right or left ear stimulus was used to tap verbal processing, attention and cognitive control, calculated as an aggregate score. When comparing the two groups, there were remaining activations in the task-present condition for the cannabis group, not seen in the no-cannabis group, while there was remaining activation in the task-absent condition for the no-cannabis group, not seen in the cannabis group. Thus, the patients with previous cannabis use showed increased activation in an effort mode network and decreased activation in the default mode network as compared to the no-cannabis group. It is concluded that the present study show some differences in brain activation to a cognitively challenging task between previous cannabis and no-cannabis schizophrenia patients.